Impact of cluster set resistance training on strength, functional capacity, metabolic and inflammatory state in older hemodialysis subjects: A randomized controlled clinical trial - Magalhães de Castro, Bruno; dos Santos Rosa, Thiago; de Araújo, Thaís Branquinho; de Luca Corrêa, Hugo; de Deus, Lysleine Alves; Neves, Rodrigo Vanerson Passos; Reis, Andrea Lucena; dos Santos, Rafael Lavarini; da Silva Barbosa, Jéssica Mycaelle; de Sousa Honorato, Fernando; da Motta Vilalva Mestrinho, Vitória Marra; Tzanno-Martins, Carmen; et al. (Experimental gerontology, 2023)
Hemodialysis-associated neuromuscular dysfunction appears to be counteracted by resistance training (RT) in older patients with chronic kidney disease (CKD). Thus, the aim of the present study was to evaluate the impact of cluster-set RT protocol on anthropometric parameters, functional capacities, and biochemical variables in older patients with CKD. Seventy-eight older patients (age: 57.55 ± 4.06 years) with CKD undergoing maintenance hemodialysis participated, and were randomly divided into control group (CG, N = 26), traditional RT (RT, N = 26) and cluster-set RT (RT-CS, N = 26) groups. Participants completed 24 weeks of RT three times per week, 1 h and 30 min before the hemodialysis session. Patients from the RT-CS group displayed increased adherence as compared to the RT group (66.35 % versus 61.73 %, p < 0.0001). There was an improvement of all anthropometric variables, handgrip strength, timed up and-go (TUG) and six-minute walking test (6MWT) following both training protocols when compared to control group and pre-intervention values. Fasting blood glucose decreased for both RT and RT-CS groups as compared with pre-intervention, without differences between training protocols and CG. Glycated hemoglobin, inflammatory cytokines, and triglycerides decreased in RT and RT-CS groups as compared with pre-intervention and CG, without differences between them. Furthermore, the RT-CS protocol resulted in a greater number of people who were responsive to training when compared to traditional training. RT-CS is a clinically valuable tool to improve anthropometric parameters, handgrip strength, TUG, 6MWT, fasting blood glucose, and cytokines in CKD older patients. •RT-CS displayed a higher quantity of responders when compared to RT.•Chronic RT-CS and RT promote similar changes on functional capacities and biochemical variables.•RT-CS and RT can be considered as non-pharmacological tools for the treatment of CKD patients.